2014
DOI: 10.1097/aog.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Postablation Risk Factors for Pain and Subsequent Hysterectomy

Abstract: Patient characteristics should be considered when counseling patients about the possible outcomes of endometrial ablation. A significant portion of ablations are complicated by postablation pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 21 publications
6
43
0
Order By: Relevance
“…In several studies, young age at endometrial ablation is a significant risk factor for hysterectomy (19)(20)(21)(22). Leiomyomas were a significant risk factor for hysterectomy in our study as well as in a large study from England (22) and in a smaller US study (23). We also found that women with postablation hysterectomy were more likely to have prior cesarean deliveries, a finding already reported (20,23).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In several studies, young age at endometrial ablation is a significant risk factor for hysterectomy (19)(20)(21)(22). Leiomyomas were a significant risk factor for hysterectomy in our study as well as in a large study from England (22) and in a smaller US study (23). We also found that women with postablation hysterectomy were more likely to have prior cesarean deliveries, a finding already reported (20,23).…”
Section: Discussionsupporting
confidence: 85%
“…Leiomyomas were a significant risk factor for hysterectomy in our study as well as in a large study from England (22) and in a smaller US study (23). We also found that women with postablation hysterectomy were more likely to have prior cesarean deliveries, a finding already reported (20,23). In our study, majority of women with endometrial ablation were sterilized, which reflects the contraception policy; in Finland sterilization is strongly recommended before endometrial ablation.…”
Section: Discussionsupporting
confidence: 83%
“…Recent US data indicate that the hysterectomy rate has remained relatively constant at 600 000 cases/year [17]. There are also concerns about the interval surgical interventions, such as reablation and/or hysterectomy, performed for recurrent menorrhagia and/or new pelvic pain [18][19][20].…”
mentioning
confidence: 99%
“…Questions and concerns have been raised about high subsequent additional surgical reintervention rates, such as reablation and/or hysterectomy performed for recurrent HMB and/or new pelvic pain. These rates are reported to range between 16% and 24% [17][18][19][20][21].…”
mentioning
confidence: 99%